How to Prepare a Project-Based Business English Presentation in the Vocational Higher Education Context? - AMANSYAH, Farida; DINO, Chenee M (Research and Innovation in Applied Linguistics, 2023)
This article presents the process of preparing project-based business English presentations in the vocational higher education context. It emphasizes the relevance of these presentations in preparing students for the workforce by developing practical skills. The article provides a comprehensive guide, covering topic selection, research, presentation organization, and the development of language and communication skills. It offers strategies for delivering engaging presentations, managing anxiety, and handling questions. The importance of evaluation, self-reflection, and ongoing improvement is highlighted. By following these guidelines, students can enhance their communication abilities, gain confidence, and effectively showcase their business English skills in a vocational higher education setting.